Enhanced Photoluminescence of Gold Nanoparticle‐Quantum Dot Hybrids Confined in Hairy Polymer Nanofibers. Issue 7 (2nd May 2021) - Singh, Sajan; Raulo, Avinash; Singh, Ajeet; Mittal, Mona; Horechyy, Andriy; Hübner, René; Formanek, Petr; Srivastava, Rajiv K.; Sapra, Sameer; Fery, Andreas; Nandan, Bhanu
Abstract: In the present work, we have studied the influence of gold nanoparticles (AuNPs) on the photoluminescence (PL) behavior of cadmium selenide (CdSe) quantum dots (QDs) confined in spatially separated soft nanoscale cylindrical domains. These cylindrical domains, in the form of hairy core‐shell nanofibers, were fabricated via cooperative self‐assembly of polystyrene‐ block ‐poly(4‐vinylpyridine) (PS‐b‐P4VP) block copolymer (BCP) mixed with pre‐synthesized CdSe QDs and AuNPs. The CdSe QDs and AuNPs were simultaneously incorporated in the P4VP cylindrical domains of the self‐assembled BCP structure. It was found that the confinement imposed by the nanometer‐sized cylindrical core resulted in the localization of the CdSe QDs and AuNPs in close proximity. Notably, it was observed that the PL intensity of the CdSe QDs could be manipulated by varying the amount of AuNPs present in the cylinder core. Interestingly, in the presence of a very low fraction of AuNPs, the PL intensity of the CdSe QDs increased compared to the AuNPs‐free system. However, further increase in the fraction of AuNPs led to gradual quenching of the photoluminescence intensity. The PL enhancement and quenching plausibly was due to the interplay between the energy transfer due to surface plasmon coupling and FRET/electron transfer from QDs to the AuNPs. The resulting functional nanofibers could have potential applications in sensing, bioimaging, and optoelectronic devices. Abstract : The interaction between CdSe quantum dots and plasmonic Au nanoparticles within the nano‐dimension geometry of cylindrical nanostructures obtained via self‐assembly process of polystyrene‐block‐poly(4‐vinylpyridine) block copolymers has been investigated. The adopted strategy enabled the manipulation of photoluminescence behaviour of CdSe QDs by simple tuning of the relative ratios between CdSe quantum dots and Au nanoparticles and was systematically studied.